2015
DOI: 10.1016/j.bspc.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Automatic cough segmentation from non-contact sound recordings in pediatric wards

Abstract: Cough is a common symptom of almost all childhood respiratory diseases. In a typical consultation session, physicians may seek for qualitative information (e.g. wetness) and quantitative information (e.g. cough frequency) either by listening to voluntary coughs or by interviewing the patients/carers. This information is useful in the differential diagnosis and in assessing the treatment outcome of the disease. The manual cough assessment is tedious, subjective, and not suitable for long-term recording. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 26 publications
2
55
1
Order By: Relevance
“…Smartphone-recorded data in different noisy scenarios (including when the device was carried in a pocket or bag) was used to validate the method. This work also demonstrated that classical feature sets such as the MFCC employed in [10], [14], [16] failed to perform on challenging noisy environments.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Smartphone-recorded data in different noisy scenarios (including when the device was carried in a pocket or bag) was used to validate the method. This work also demonstrated that classical feature sets such as the MFCC employed in [10], [14], [16] failed to perform on challenging noisy environments.…”
mentioning
confidence: 85%
“…The operation of these devices relies on pattern recognition engines primarily based on features extracted from cough sounds and complementary signals like electromyography of chest movement. However, many of these systems have only been tested in controlled environments where patients did not perform any movement or physical activity [9], [10] or force the users to wear complex recording systems [9], [11]. A portable cough monitor relying on audio recordings and able to cope with noisy real-life environments could be implemented on a smartphone for continuous real-time monitoring of respiratory patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their system is hence able to protect personal privacy. Amrulloh et al attempted to design an automated method to automatically identify cough segments from the pediatric sound recordings and achieved a sensitivity and specificity of 93% and 98%, respectively [5].…”
Section: Audio-only Coughmentioning
confidence: 99%
“…This symptom is also the very reason why people seek medical advice in America and China [1,2]. Even though the importance of cough diagnosis is well admitted by academic organizations [2][3][4] in recent years, there is no gold standard to assess cough due to the lack of objective and accurate measures of cough frequency and severity [5]. When cough becomes chronic, it is so extremely unpleasant and distressing that the life quality of chronic cough patients has significant reductions [6].…”
Section: Introductionmentioning
confidence: 99%